Haematological evaluation of pregnant ewes fed broiler-litter based diets (2010)
Blood is a transport medium for the body which plays an active role in sustainability and survival of the organism. Haematological indices reflect the effect of dietary treatments on the animal especially the type and amount of feed ingested and available for the animal to meet its body requirements. A study was carried out for 10 weeks to assess changes in some haematological indices with advancing pregnancy in ewes fed Broiler Litter (BL) based rations. Blood samples were collected at each trimester of pregnancy and analyzed for Packed Cell Volume (PCV), Red Blood Cell (RBC), White Blood Cell (WBC) counts and Haemoglobin (Hb) concentration. Other parameters estimated were: Mean Corpuscular Value (MCV) and Mean Corpuscular Haemoglobin Concentration (MCHC). Results showed that in the first trimester, PCV and Hb. values were significantly higher (P<0.05) in animals fed at 0%, 25%, 50% and 75% BL inclusion levels. In the second trimester, RBC values decreased with increasing levels of BL in the diet while other parameters studied were not significantly different. The findings of this study showed that livestock farmers in the tropics can include broiler litter as feed supplement up to 25% without any adverse effect on the blood chemistry.